2010
DOI: 10.1016/j.jvs.2009.12.049
|View full text |Cite
|
Sign up to set email alerts
|

Duodenocaval fistula as a result of a fish bone perforation

Abstract: Duodenocaval fistula is a rare and potentially lethal condition. We report a case of a 61-year-old female with a duodenocaval fistula resulting from a fish bone perforation of the duodenum who survived with conservative treatment. To our knowledge, this is the first reported case of a duodenocaval fistula caused by a fish bone. Additionally, besides revising the other possible etiologies for duodenocaval fistulae, we also discuss its diagnosis and treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…6 Other minor risk factors for accidental fish bone ingestion include fast eating, extremes of age (children or elderly), alcohol abuse and mental retardation. 6,8 Fish bone perforation of the GI tract has several clinical manifestations, such as abdominal pain, vomiting and fever, occasionally including melena and bowel obstruction. In addition, the patients are often unaware of the accidental fish bone ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other minor risk factors for accidental fish bone ingestion include fast eating, extremes of age (children or elderly), alcohol abuse and mental retardation. 6,8 Fish bone perforation of the GI tract has several clinical manifestations, such as abdominal pain, vomiting and fever, occasionally including melena and bowel obstruction. In addition, the patients are often unaware of the accidental fish bone ingestion.…”
Section: Discussionmentioning
confidence: 99%
“…However, some cases have been successfully treated using antibiotics alone. [12][13][14][15] For chronic cases, we suggest starting with antibiotic treatment to reduce any inflammation, followed by drainage of the abscess and removal of the foreign body. This is because minimization of the inflammation will facilitate any surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] This typically arises as a complication from trauma, peptic ulcer disease, or migration of ingested foreign bodies. 6 Guillem et al 4 reported 37 cases of DCF with literature review.…”
Section: Discussionmentioning
confidence: 99%
“…When a DCF is diagnosed, patients are usually septic and unstable, leading to prompt surgery. 3 Regarding DCF with foreign body ingestion, eight patients have been reported in the English-language literature. [9][10][11][12][13] Six of these cases were due to toothpicks, one due to bone fragments, and one due to a fish bone.…”
Section: Discussionmentioning
confidence: 99%